On the relative logarithmic connections and relative residue formula - Misra, Snehajit; Singh, Anoop (Taylor and Francis Ltd., 2022)
We investigate the relative logarithmic connections on a holomorphic vector bundle over a complex analytic family. We give a sufficient condition for the existence of a relative logarithmic connection on a holomorphic vector bundle singular over a relative simple normal crossing divisor. We define the relative residue of relative logarithmic connection and express relative Chern classes of a holomorphic vector bundle in terms of relative residues.
This paper published with affiliation IIT (BHU), Varanasi in open access mode.
Keywords: Relative Chern class; relative logarithmic connection; relative residue